The state of software development teams after covid-19 - Nekhymchuk, Valeriya (2025)
This master's thesis investigates the impact of the pandemic on software development teams. The study aims to provide insights into the changes and challenges faced by software development teams during and after the pandemic. The first subgoal is to outline how software development teams functioned before the pandemic. The second is to explore key factors influencing team effectiveness, such as productivity and well-being. The third subgoal examines how the pandemic disrupted team practices, tools and communication. The final subgoal evaluates how teams adapted, drawing on interview findings to assess current work models and the effectiveness of remote and hybrid collaboration. The theoretical component of this research is grounded in a comprehensive literature review covering various dimensions of software team collaboration, agile methodologies, project management, productivity metrics and employee well-being. The theoretical part provides a background and context for the practical part of the research. The practical part of the study provides a qualitative study in a form of semi-structured interviews with software development team members. The practical research aims to collect empirical data to investigate research goals of the study. The data analysis follows a thematic analysis approach, resulting in six prominent themes: the sudden transition and initial disruption, structured communication and loss of informality, shifting productivity and personal adaptation, the increased importance of documentation and tooling, redefined team practices and preferences for hybrid and flexible work models. The final part of the study discusses the findings and their implications for the software development industry. The discussion compares the study's findings with the literature review, interprets the results and impact. Further, it provides recommendations for software development companies and provides limitations and future research directions.